2018
DOI: 10.32468/be.1060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interest Rate Caps on Financial Inclusion

Abstract: In this paper we study the liberalization of the microcredit usury rate in Colombia and its effects on loan expansion. Namely, in February 2007 the interest rate ceiling for microcredit loans was lifted and fixed to 33%, while the ceiling of all other loans remained unchanged and close to 20%. We perform a Difference-inDifference analysis by comparing the expansion of microcredit loans (treatment group) with that of corporate loans (control group). Additionally, we narrow in on similar levels of both loan size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Usury laws are rules governing interest rates that can be charged on a loan by a financial institution and target the practice of charging excessively high rates on credit facilities by introducing caps on maximum interest rate amounts which is designed to protect consumers (Benmelech & Maskowitz, 2016). Miller (2013) concluded that although there were glaring market failures in credit markets, Governments through their Central banks do not have a role in managing these market failures. Interest rates capping is not the best solution in meeting the lower interest rates.…”
Section: Introductionmentioning
confidence: 99%
“…Usury laws are rules governing interest rates that can be charged on a loan by a financial institution and target the practice of charging excessively high rates on credit facilities by introducing caps on maximum interest rate amounts which is designed to protect consumers (Benmelech & Maskowitz, 2016). Miller (2013) concluded that although there were glaring market failures in credit markets, Governments through their Central banks do not have a role in managing these market failures. Interest rates capping is not the best solution in meeting the lower interest rates.…”
Section: Introductionmentioning
confidence: 99%